Accompanying School Children Through The Literacy Tourism Program at Indonesian Literacy Homes - Rachma Oriza Sativany; Purwowibowo; Arif (Jurnal sosial dan sains, 2024)
Background: During the COVID-19 period, children were forced to study at home with limited learning facilities. They cannot develop their potential talents due to the lack of interaction between teachers and students, which results in school children not being able to optimally meet their learning needs. Purpose: This study aims to describe the assistance of school children through the literacy tourism program at the Indonesian Literacy House. The research approach uses descriptive qualitative, data collection techniques such as frank or disguised observations, semi-structured interviews, and documentation studies. Methods: Data analysis through data collection, reduction, presentation, and conclusions. Results: The results of this study show that there are four stages in assisting school children at the Indonesian Literacy House, namely registration, preparation, implementation, and evaluation. Conclusion: The Indonesian Literacy House as a non-profit institution engaged in education intervenes through a literacy tourism program, namely tourism-based assistance for school children by utilizing local wisdom resources to solve the problem of basic educational needs of school children.